Penerapan Model Kognitif Beck untuk Mengurangi Kecemasan pada Karyawan, Sektor Energi: Studi Kasus - Hardaning Prayacita; M.G.Bagus Ani Putra (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Anxiety is one of the most common psychological problems experienced by employees as a result of high job demands, unpredictable work situations, and increasing occupational pressures. If not managed adaptively, anxiety may negatively affect psychological well-being, trigger physiological symptoms, and interfere with individuals' ability to perform their daily activities effectively. This study aimed to examine the application of Beck's Cognitive Model in reducing anxiety among an employee in the energy sector. The study employed a Single Subject Research (SSR) approach using a single-case study design involving a 41-year-old male employee working in an energy company under a shift-work system. Data were collected through semi-structured clinical interviews, behavioral observations, the Depression Anxiety Stress Scale (DASS-42), the Culture Fair Intelligence Test (CFIT), the Personality and Preference Inventory (PAPI Kostick), and genogram analysis. The assessment results indicated that the participant experienced severe anxiety, while depression and stress remained within the normal range. The CFIT results showed average intellectual functioning (IQ = 106), whereas the PAPI Kostick assessment revealed personality characteristics marked by a strong preference for structure and certainty, limited flexibility toward change, and a tendency to suppress emotional expression. The intervention consisted of three sessions focusing on anxiety psychoeducation, identification of automatic thoughts, cognitive restructuring based on Beck's Cognitive Model, and the development of adaptive emotional regulation and coping strategies. The intervention resulted in a reduction in anxiety symptoms, improved awareness of the relationship between thoughts, emotions, and physiological responses, and the development of more realistic cognitive appraisals when facing uncertain situations. These findings suggest that the application of Beck's Cognitive Model can effectively reduce anxiety among employees experiencing psychological distress related to occupational demands and changing work conditions.